The Impact of Using a Distance Learning Network on Building Teachers' Communities of Practice in Egypt - Gouda, Amal; Banks, Frank (Proceedings of the International Conference on Networked Learning, 2006)
This research is a case study of using a distance learning network for teachers' professional development in Egypt. It aims to investigate the impact of using Egypt's National Network for Distance Training (NNDT) in developing teachers' knowledge and on building communities of practice. It explores the role of professional development experts and teachers' participation within the network. In addition, it draws attention to the teachers' level of engagement in professional development programmes and, therefore, it reveals their modes of participation within the network. Moreover, it identifies the role of the technology in facilitating communication and collaboration between participants. Finally, this paper offers a number of recommendations that aim to develop the network capabilities to become a more 'effective' means for teachers' professional development in Egypt.